Pyloric Gland Adenoma in Lynch Syndrome - Lee, Seung Eun (Raven Press, 2014)
The prevalence of gastric cancer associated with Lynch syndrome (LS) is highly variable, and the underlying histologic pathway or molecular mechanisms remain unclear. From 1995 to 2012, 15 patients had been treated for both gastric and colonic adenocarcinomas and diagnosed as LS. In all cases, pathologic review, immunohistochemical analysis for mismatch-repair proteins, and microsatellite instability (MSI) tests were performed. To confirm LS, germline mutation tests and multiplex ligation-dependent probe amplification were performed. All gastric and colonic carcinomas were MSI-high and lost expressions of MLH1/PMS2 in 11 (73%) cases and MSH2/MSH6 in 4 (27%) cases. Remarkably, in a patient with LS and germline mutation of MLH1 gene, pyloric gland adenoma (PGA) transformed to adenocarcinoma during follow-up. In 2 additional cases, PGA was found adjacent to advanced gastric cancers. All PGAs in LS patients were MSI-high and lost expression of mismatch-repair proteins (MLH1/PMS2 in 2 cases and MSH2/MSH6 in 1 case), whereas none of the 14 sporadic PGAs was MSI-high or had lost expression of mismatch-repair proteins. On the basis of these observations, although very rare, we suggest the possibility that PGA may be a precursor lesion to gastric adenocarcinoma in LS and that the mismatch-repair deficient pathway of carcinogenesis is involved early in the gastric carcinogenesis pathway.